High frequency oscillations mirror disease activity in patients with focal cortical dysplasia. Issue 8 (30th July 2013) - Kerber, Karolin; LeVan, Pierre; Dümpelmann, Matthias; Fauser, Susanne; Korinthenberg, Rudolf; Schulze‐Bonhage, Andreas; Jacobs, Julia
Summary Purpose The study analyzes the occurrence of high frequency oscillations in different types of focal cortical dysplasia in 22 patients with refractory epilepsy. High frequency oscillations are biomarkers for epileptic tissue, but it is unknown whether they can reflect increasingly dysplastic tissue changes as well as epileptic disease activity. Methods High frequency oscillations (80–450 Hz) were visually marked by two independent reviewers in all channels of intracranial implanted grid, strips, and depth electrodes in patients with focal cortical dysplasia and refractory epilepsy. Rates of high frequency oscillations in patients with pathologically confirmed focal cortical dysplasia of Palmini type 1a and b were compared with those in type 2a and b. Key Findings Patients with focal cortical dysplasia type 2 had significantly more seizures than those with type 1 (p < 0.001). Rates of high frequency oscillations were significantly higher in patients with focal cortical dysplasia type 2 versus type 1 (p < 0.001). In addition, it could be confirmed that rates of high frequency oscillations were significantly higher in presumed epileptogenic areas than outside (p < 0.001). Significance Activity of high frequency oscillations mirrors the higher epileptogenicity of focal cortical dysplasia type 2 lesions compared to type 1 lesions. Therefore, rates of high frequency oscillations can reflect disease activity of a lesion. This has implications for the use of high frequency oscillations as biomarkers for epileptogenic areas, because a detailed analysis of their rates may be necessary to use high frequency oscillations as a predictive tool in epilepsy surgery.